Analysis of metabolic equivalents and energy expenditure in a high-intensity functional training session in physically active subjects - Bustos-Viviescas, Brian Johan (2025)
Introduction: Research regarding metabolic equivalents and energy expenditure in high-intensity functional training sessions is scarce despite the popularity of this fitness modality. Objective: To analyze metabolic equivalents and energy expenditure in a high-intensity functional training session in physically active subjects. Methodology: Descriptive study of quantitative approach with a sample at convenience of 14 men (age 23,21±2,26 years; body mass 70,52±10,61 kg; height 1,75±0,06 m) and 7 women (age 23,60±1,67 years; body mass 57,76±10,38 kg; height 1,58±0,06 m) physically active. They performed the WOD Karen (150 wall balls) and the heart rate was recorded every 30 repetitions through the H7 heart rate monitors. Metabolic equivalents were determined with respect to maximum heart rate (HRmax) and maximal oxygen consumption data obtained in a field test, while energy expenditure was estimated from a predictive equation. Statistical analysis was carried out in the statistical package PSPP (95% confidence and a p-value of 0,05). Results: Men obtained 12,96±1,18 MET and women 12,17±0,93 MET, the energy expenditure of men was 73,92±7,54 kJ.min-1 and in women 51,89±3,15 kJ.min-1. Conclusion: A high-intensity functional training session presents submaximal to maximal values in physically active subjects.